A new therapeutic approach for type 1 diabetes: Rationale for GNbAC1, an anti‐HERV‐W‐Env monoclonal antibody. Issue 9 (10th June 2018) - Curtin, Francois; Bernard, Corinne; Levet, Sandrine; Perron, Hervé; Porchet, Hervé; Médina, Julie; Malpass, Sam; Lloyd, David; Simpson, Richard; ,
Abstract : We describe a newly identified therapeutic target for type 1 diabetes (T1D): an envelope protein of endogenous retroviral origin, human endogenous retrovirus W envelope (HERV‐W‐Env). HERV‐W‐Env was found to be detected in the blood of ~60% of patients with T1D and is expressed in acinar pancreatic cells of 75% of patients with T1D at post mortem examination. Preclinical experiments showed that this protein displays direct cytotoxicity on human β‐islet cells. In vivo HERV‐W‐Env impairs the insulin and glucose metabolism in transgenic mice expressing HERV‐W‐Env. GNbAC1, an IgG4 monoclonal antibody, has been developed to specifically target HERV‐W‐Env and to neutralize the effect of HERV‐W‐Env in vitro and in vivo . GNbAC1 is currently in clinical development for multiple sclerosis and > 300 subjects have been administered with GNbAC1 so far. GNbAC1 is now being tested in T1D in the RAINBOW‐T1D study, which is a randomized placebo‐controlled study with the objective of showing the safety and pharmacodynamic response of GNbAC1 in patients who have had T1D with a maximum of 4 years' duration. GNbAC1 is being tested vs placebo at the dose of 6 mg/kg in 60 patients during six repeated administrations for 6 months; a 6‐month open‐label extension will follow. The primary endpoint is to assess safety, and secondary endpoints are the pharmacodynamic responses to GNbAC1. GNbAC1 targeting HERV‐W‐Env is currently in clinical development in T1D, with the first safety and pharmacodynamic study. If the study results are positive, this may open the door to the development of an innovative non‐immunomodulatory disease‐modifying treatment for T1D.